2014
DOI: 10.1186/1471-2407-14-952
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic influence of cyclooxygenase-2 protein and mRNA expression in node-negative breast cancer patients

Abstract: BackgroundCyclooxygenases (COX) play a key role in prostaglandin metabolism and are important for tumor development and progression. The aim of this study was to analyze the prognostic impact of COX-2 expression in a cohort of lymph node-negative breast cancer patients not treated in the adjuvant setting.MethodsCOX-2 expression was determined by immunohistochemistry (IHC) in tumor tissue of 193 node-negative breast cancer patients. Additionally, mRNA expression was determined in corresponding tumor samples usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…The association between COX‐2 expression and prognosis remained significant after multivariable adjustments only in two smaller studies with around 200 patients, but not in the two largest studies with 1,576 and 2,001 patients, respectively . In other studies, COX‐2 was only independently associated with worse prognosis in subgroups of patients who were either node‐negative, had high Ki67, ER‐negative, or ER‐positive tumors . There are many possible explanations for the diverse results between previous studies including study populations with different body constitutions, reproductive patterns, lifestyle factors, medication use, ethnic backgrounds, and study end‐points.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The association between COX‐2 expression and prognosis remained significant after multivariable adjustments only in two smaller studies with around 200 patients, but not in the two largest studies with 1,576 and 2,001 patients, respectively . In other studies, COX‐2 was only independently associated with worse prognosis in subgroups of patients who were either node‐negative, had high Ki67, ER‐negative, or ER‐positive tumors . There are many possible explanations for the diverse results between previous studies including study populations with different body constitutions, reproductive patterns, lifestyle factors, medication use, ethnic backgrounds, and study end‐points.…”
Section: Discussionmentioning
confidence: 88%
“…Tumor COX‐2 expression has previously been associated with a shorter disease‐free survival in many but not all studies. However, most of the previous studies had 200 patients or less . Further, multivariable analyses to elucidate the independent prognostic value of COX‐2 expression, were only performed in a subset of these studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One key inflammatory mediator deregulated in many cancers is cyclooxygenase-2 (COX-2). Elevated COX-2 expression, and that of its principle metabolic product prostaglandin E2 (PGE 2 ), has been shown to be inversely associated with patient survival [2527]. Epidemiological, clinical, and preclinical studies have shown that the inhibition of PGE 2 synthesis through the use of either nonsteroidal anti-inflammatory drugs (NSAIDs) or specific COX-2 inhibitors has the potential to reduce the risk of developing certain cancers, including breast, head and neck squamous cell carcinoma, osteosarcoma, pancreas, and prostate cancers, and to reduce the mortality caused by these cancers [2835].…”
Section: Introductionmentioning
confidence: 99%